Stochastic processes in the structure and functioning of soil biodiversity - Lindo, Zoë; Bolger, Thomas; Caruso, Tancredi (Frontiers in Ecology and Evolution, 2023)
Ecologists are increasingly recognising the importance of stochastic processes in generating spatial and temporal variation in biological communities. This variation is very high in soil, which hosts not less than ¼ of all biodiversity on Earth and is central to how the terrestrial ecosystem responds to perturbations. Measurement errors, demographic stochasticity (individual variability in traits such as birth and death rates), and environmental stochasticity (fluctuations in environmental properties) are the three main sources of stochasticity in ecology. Here we synthesise how these three sources of stochasticity are quantified and incorporated in the study of soil biodiversity, highlighting current limits, possible solutions and future research needs. We stress the relevance of all these factors to our future understanding of terrestrial ecosystems via plant-soil interactions and soil-climate feedbacks. In soil, the major sources of stochasticity are measurement errors and environmental stochasticity. Measurement errors are due to the small size, high abundance, and broad distributions of soil organisms, which limit sampling in space and especially over time. We argue that positive autocorrelation is a main characteristic of soil environmental properties, which may have important consequences on the response of soil biota to perturbations. At a local scale, large populations of soil organisms also imply a minor role of demographic stochasticity. Yet, we show that demographic stochasticity can be sizeable in some datasets but still much smaller than environmental stochasticity. Explicit consideration of stochastic processes in soil biodiversity research is essential to our future understanding of the processes that control soil biodiversity. In classical ecology, stochasticity implies probabilistic predictions in terms of population growth, extinction, species coexistence and community diversity. In soil, stochasticity implies very variable responses to climate change and the soil-climate feedback. Future studies will have to identify the major sources of environmental stochasticity with a particular focus on the interaction between multiple global change factors.